Effect of Da-Cheng-Qi Decoction on Pancreatitis-Associated Intestinal Dysmotility in Patients and in Rat Models. (2nd March 2015) - Zhao, Jianlei; Zhong, Cejun; He, Zhiyu; Chen, Guangyuan; Tang, Wenfu
Abstract : The impairment of intestinal motility and related infectious complications are the predominant clinical phenomenon in patients with severe acute pancreatitis (SAP). We aimed to investigate the effects of Da-Cheng-Qi decoction (DCQD) on the gastrointestinal injury in SAP patients and the potential mechanism involved in rats. DCQD was enema administered to 70 patients for 7 days in West China Hospital. Mortality and organ failure during admission were observed and blood samples for laboratory analysis were collected. We also experimentally examined plasma inflammatory cytokines in rat serum and carried the morphometric studies of the gut. Intestinal propulsion index and serum and tissue vasoactive intestinal peptide (VIP) were also detected. Though DCQD did not affect the overall incidence of organ failure, it shortened the average time of paralytic intestinal obstruction and decreased the morbidity of infectious complications in patients with SAP. Compared with untreated rats, the DCQD lowered the levels of proinflammatory cytokine and decreased the mean pathological intestinal lesion scores. The VIP level in intestinal tissue or serum in DCQD group was obviously lowered and intestinal propulsion index was significantly improved. In conclusion, DCQD has good effect on pancreatitis-associated intestinal dysmotility in patients and in rat models.